Evaluation of anaerobic digestion of low-concentration wastewater in one and two stages at laboratory scale - Centeno-Mora, Erick (2025)
This article addresses the growing need for efficient and sustainable methods for wastewater treatment in Costa Rica, with a specific focus on two-stage anaerobic digestion of low-concentration wastewater, for both municipal wastewater and synthetic effluents. The anaerobic digestion of low-concentration wastewater was evaluated in anaerobic reactors with a support medium at a laboratory scale. The behavior of anaerobic digestion in one and two stages for municipal and synthetic (glucose) wastewater was compared, monitoring various system parameters, including organic matter removal efficiency, pH, alkalinity, Redox potential, and biogas production potential. The results revealed that for rapidly biodegradable effluents such as glucose, anaerobic digestion in two stages offers significant advantages, such as greater process stability and increased biogas production. However, challenges were encountered in treating ordinary wastewater, indicating the need for further research to refine the method. Two-stage digestion was found to be less convenient for these waters due to the stability already achieved in a single reactor and the added complexity of operating two stages. In conclusion, the study highlights the potential of two-stage anaerobic digestion in the treatment of low organic concentration wastewater, particularly for rapidly biodegradable substances, and points out areas for future research and process optimization.